2012
DOI: 10.5601/jelem.2009.14.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical composition of selected winter wheat species

Abstract: Chemical composition of common wheat-Triticum aestivum ssp. vulgare Vill. Host., hard wheat-Triticum durum Desf., and spelt-Triticum aestivum ssp. spelta (L.) Thell grains was investigated. Total protein, wet gluten, fiber, ash, carbohydrates, falling number, macronutrients (phosphorus, potassium, calcium, magnesium), and microelements (copper, iron, manganese, zinc) were determined. Also standard deviation, variability and correlation coefficients were calculated. Hard wheat and spelt lines were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…Overall, our results of chemical analyses were in agreement with results from previous studies (Fiems, De Boever, Vanacker, De Campeneere, & De Brabander, ; Ingalls, Morgan, Thomas, & Huffman, ; Lecomte, ; Rachoń & Szumiło, ). The average energy concentration of hulled spelt (11.7 MJ ME/kg DM, 7.3 MJ NEL/kg DM) was comparable to that of oats (11.5 MJ ME kg ‐1 DM, 7.0 MJ NEL/kg DM; DLG, ).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results of chemical analyses were in agreement with results from previous studies (Fiems, De Boever, Vanacker, De Campeneere, & De Brabander, ; Ingalls, Morgan, Thomas, & Huffman, ; Lecomte, ; Rachoń & Szumiło, ). The average energy concentration of hulled spelt (11.7 MJ ME/kg DM, 7.3 MJ NEL/kg DM) was comparable to that of oats (11.5 MJ ME kg ‐1 DM, 7.0 MJ NEL/kg DM; DLG, ).…”
Section: Discussionsupporting
confidence: 92%
“…Spelt grain is characterized by higher protein content than bread wheat grain (Kohajdová, Karovičová, 2008;Rachoń, Szumiło, 2009;Escarnot et al, 2012). According to Mikos and Podolska (2012) and Świeca et al (2014), total protein content in spelt variety 'Schwabenkorn' grain varies within a wide range from 13.2% to 15.5%.…”
Section: Resultsmentioning
confidence: 99%
“…In the current research, it was found that supplementing mineral fertilisation with micronutrients did not have a significant effect on the Application of mineral fertilisers with micronutrients results in a higher yield and content of mineral components in grain (Narimani et al, 2010;Nadim et al, 2012). The nutritive value of spelt grain is high -the grain contains all necessary nutrients (Rachoń, Szumiło, 2009;Rachoń et al, 2015). Those authors found that, regardless of the micronutrients applied, the grain of spelt variety 'Schwabenkorn' contained more Cu, Mn and Fe compared to the finding of Kraska et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard wheat cv. Tonacja is characterized by macroelements contents in grain dry matter at the levels of: phosphorus 3.8 g•kg -1 , potassium 4.2 g•kg -1 , magnesium 1.3 g•kg -1 , and calcium 0.34 g•kg -1 (Rachoñ and Szumi³o 2009). Assessment of these macroelements in grains of wheat reveals that it was very similar to the standard.…”
Section: Contents Of Macro-and Microelements In Grains Of Spring Wheatmentioning
confidence: 96%